The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1007/s10533-009-9326-8
|View full text |Cite
|
Sign up to set email alerts
|

Release and uptake of volatile inorganic and organic gases through the snowpack at Niwot Ridge, Colorado

Abstract: Whole air drawn from four heights within the high elevation (3,340 m asl), deep, winter snowpack at Niwot Ridge, Colorado, were sampled into stainless steel canisters, and subsequently analyzed by gas chromatography for 51 volatile inorganic and organic gases. Two adjacent plots with similar snow cover were sampled, one over bare soil and a second one from within a snow-filled chamber where Tedlar/ Teflon-film covered the ground and isolated it from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…More than 50 volatile gases were determined by gas chromatography in whole air flask samples collected from the two snow sampling towers. Results from these measurements reported in Helmig et al (2009a) clearly show how the NWT snowpack functions as a source of trace gas species, and the release rates for CHCl 3 , dimethylsulfide, CS 2 , and CHCl 3 add four more compounds to the list of gas emissions that previously have been reported from snow-covered ecosystems. The complexity of the snowpack behavior is exemplified by the fact that for 19 other gases uptake to the snow was observed.…”
Section: Helmig Et Al (Voc; Soddie Site)mentioning
confidence: 82%
See 1 more Smart Citation
“…More than 50 volatile gases were determined by gas chromatography in whole air flask samples collected from the two snow sampling towers. Results from these measurements reported in Helmig et al (2009a) clearly show how the NWT snowpack functions as a source of trace gas species, and the release rates for CHCl 3 , dimethylsulfide, CS 2 , and CHCl 3 add four more compounds to the list of gas emissions that previously have been reported from snow-covered ecosystems. The complexity of the snowpack behavior is exemplified by the fact that for 19 other gases uptake to the snow was observed.…”
Section: Helmig Et Al (Voc; Soddie Site)mentioning
confidence: 82%
“…Follow-up research in seasonal snow collected in Northern Michigan (Honrath et al 2000) suggested that similarly NO may be produced and released from mid-latitude snow. Helmig et al (2009a) at the Soddie site showed enhanced (NO ? NO 2 ) levels in the snow, with interstitial air concentrations at times exceeding ambient air levels (above the snow surface) by a factor of 10-50.…”
Section: Williams Et Al (Snow and Water Chemistry; Soddie Site)mentioning
confidence: 99%
“…It has been discussed previously that photochemistry of organic compounds changes the composition of the snowpack/ice impurities (Klan and Holoubek, 2002) and leads to VOC production (Grannas et al, 2007b). Helmig et al (2009) showed that the snowpack can act as a source for some gas phase species (CO 2 , CHCl 3 , (CH 3 ) 2 S, CS 2 , CHBrCl 2 ) or as a sink for others (CO, COS, some halogenated compounds and hydrocarbons). Biological activity in snow and sea ice is another important but asyet poorly constrained source of VOCs (Ariya et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…At the C1 site, there are continuous data for the whole winter for CO 2 , and a single day of measurements of N 2 O and VOCs (Swanson et al 2005). At the Soddie site, there are continuous data for the whole winter for CO 2 ), N 2 O (Filippa et al 2009), and O 3 and NO x (Helmig, Apel, et al 2009), and several days of data for Hg (Faïn et al 2013) and VOCs and CH 4 ). The subalpine Soddie and C1 sites differ by several hundred metres in elevation but also in the landscape setting.…”
Section: Introductionmentioning
confidence: 99%